2004
DOI: 10.1002/cncr.20644
|View full text |Cite
|
Sign up to set email alerts
|

Identification of progressive cervical epithelial cell abnormalities using DNA image cytometry

Abstract: BACKGROUND The objectives of the current study were to compare the capabilities of conventional cervical cytology and of DNA image cytometry (DNA‐ICM) in the prediction of progressive or regressive behavior in atypical squamous cells (ASC), low‐grade squamous intraepithelial lesions (LSIL), and atypical glandular cells (AGC). METHODS One hundred ninety‐six women with Papanicolaou (Pap) smears that yielded diagnoses of ASC, LSIL, or AGC were included in a prospective cohort study. Slides were classified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 33 publications
0
51
0
1
Order By: Relevance
“…This is not necessarily surprising, given that HSILs and invasive carcinomas share many morphologic and molecular characteristics. Like invasive cervical carcinomas, HSILs are clonal, frequently aneuploid, and often harbor integrated HPV DNA (9,(29)(30)(31)(32). One recent study that used DNA microarray data to identify chromosomal copy number alterations in preinvasive and invasive cervical carcinomas showed gains of chromosomes 12q and losses of 12p in both types of lesions (33).…”
Section: Discussionmentioning
confidence: 99%
“…This is not necessarily surprising, given that HSILs and invasive carcinomas share many morphologic and molecular characteristics. Like invasive cervical carcinomas, HSILs are clonal, frequently aneuploid, and often harbor integrated HPV DNA (9,(29)(30)(31)(32). One recent study that used DNA microarray data to identify chromosomal copy number alterations in preinvasive and invasive cervical carcinomas showed gains of chromosomes 12q and losses of 12p in both types of lesions (33).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have reported a strong association between highly aneuploid squamous cells and HR-HPV [62] as well as a positive predictive value of 81.8% for CIN 2 for 9c cells [63]. A prospective study by Grote et al demonstrated a significant increase in DNA aneuploidy in cervical cytology material from patients with CIN 1 (54%) and CIN 2 (64.3%) to CIN 3 or greater (83.3%) on subsequent biopsies [64]. In a preliminary retrospective study assessing the utility of DNA ploidy in the management of ASC cytology specimens, Lorenzato et al suggest that the combined use of HR-HPV testing and DNA ploidy measurement on ASCUS cytology specimens may improve the triage of women who have to undergo colposcopy as well as identify patients with a diagnosis of ASC-H at higher risk for CIN 2 or greater lesions [65].…”
Section: Dna Aneuploidymentioning
confidence: 99%
“…The median interval between the initial "atypical" smear and the subsequent histological grading into "cervical intraepithelial neoplasia (CIN) status I-III" was 3 months. 53 During this interval 65% of the aneuploid atypical samples, but only 35% of the total atypical samples developed a neoplastic status of > CIN II. Moreover, "DNA image cytology" correctly predicted that the majority of diploid or near diploid atypical samples did not progress to a neoplastic state, "non-progression within 6 months was 85%".…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%